Pavement Characteristics Affecting The Frequency Content Of Tire/Pavement Noise - Öngel, Aybike; Harvey, John (Inst Noise Control Engineering, Iowa State Univ, College Engineering, 212 Marston Hall, Ames, Ia 50011-2152 Usa, 2010)
Tire/pavement noise is a major contributor to traffic noise at highway speeds. Annoyance is more closely related to frequency content than to overall A-weighted noise levels, therefore spectral content analysis of tire/pavement noise is an important consideration. A study conducted in California measured the noise levels of different mix types and the pavement characteristics affecting noise levels as determined by on-board sound intensity (AASHTO TP 76-08). Data was collected on dense-graded asphalt concrete mixes (DGAC), conventional open-graded mixes (OGAC), open-graded rubberized asphalt concrete mixes (RAC-O), and gap-graded rubberized asphalt concrete mixes (RAC-G) with ages less than 8 years old. This paper evaluates the effects of pavement characteristics including the air-void content, gradation properties, rubber inclusion, roughness, texture, pavement surface condition, and age on one-third octave band noise levels. This research confirmed that macrotexture and IRI, which are associated with the impact and shock mechanisms, increase the noise levels at lower frequencies. Higher air-void content, associated with the air pumping mechanism, reduces the noise levels at higher frequencies. (C) 2010 Institute of Noise Control Engineering.
Keywords: road traffic noise; components; annoyance; trafik gürültüsü; bileşenler; sıkıntı